2019
DOI: 10.1002/jor.24484
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Pelvic Tilt From Supine to Standing in Patients With Symptomatic Developmental Dysplasia of the Hip

Abstract: Pelvic sagittal inclination (PSI) significantly affects the femoral head coverage by the acetabulum in patients with developmental dysplasia of the hip (DDH), while no reports have quantified PSI in DDH patients in the supine and standing positions. Furthermore, little is known about how PSI changes after periacetabular osteotomies. Herein, PSI in the supine and standing positions was quantified in DDH patients preoperatively and postoperatively. Twenty‐five patients with DDH who had undergone periacetabular o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 35 publications
3
40
3
Order By: Relevance
“…Second, the observed pelvic tilt in our cohort is equivalent to that found in the normal population (7.2°–12°) [ 27–29 ], and in patients with acetabular dysplasia (8.3° pre- and 6.2° post-PAO) [ 17 ]. Third, the pre-operative pelvic tilt in our cohort of patients with anterolateral undercoverage was not significantly higher than that seen in patients with symptomatic acetabular retroversion, as demonstrated by Grammatopoulos et al (4° ± 4°) [ 11 ].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Second, the observed pelvic tilt in our cohort is equivalent to that found in the normal population (7.2°–12°) [ 27–29 ], and in patients with acetabular dysplasia (8.3° pre- and 6.2° post-PAO) [ 17 ]. Third, the pre-operative pelvic tilt in our cohort of patients with anterolateral undercoverage was not significantly higher than that seen in patients with symptomatic acetabular retroversion, as demonstrated by Grammatopoulos et al (4° ± 4°) [ 11 ].…”
Section: Discussionsupporting
confidence: 68%
“…These findings are supported by those of Tani et al . who evaluated the pelvic sagittal inclination (PSI) in patients with acetabular dysplasia with anterolateral under coverage and demonstrated neither significant difference in the pre-operative and post-operative PSI, nor the change in PSI [ 17 ]. Grammatopoulos et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collectively, our results indicate that change in regional coverage can be assumed by understanding the change in the PSI and confirmed the clinical importance of previous studies that quantified PSI in several postures for participants with FAIS and DDH. Recently, one study found a small change in PSI in the standing position following peri‐acetabular osteotomy as the PSI in supine and standing positions varied (Tani et al, 2019). The authors suggested that the PSI in the standing position should be referenced when developing surgical plans for peri‐acetabular osteotomy, which can be supported by our findings that PSI affects head coverage, especially in the anterior region.…”
Section: Discussionmentioning
confidence: 99%